Writing architectures : ficto-critical approaches - Frichot, Hélène; Stead, Naomi (London, UK : Bloomsbury Visual Arts, 2020)
Architects and fiction writers share the same ambition: to imagine new worlds into being. Every architectural proposition is a kind of fiction before it becomes a built fact; likewise, every written fiction relies on the construction of a context in which a story can take place. This collection of essays explores what happens when fiction, experimental writing and criticism are combined and applied to architectural projects and problems. It begins with ficto-criticism -- an experimental and often feminist mode of writing which fuses the forms and genres of essay, critique, and story -- and extends it into the domain of architecture, challenging assumptions about our contemporary social and political realities, and placing architecture in contact with such disciplines as cultural studies, literary theory and ethnography. These sixteen newly-written pieces have been selected for this volume to show how ficto-critical writing can be a powerful vehicle for creative architectural practice, providing new opportunities to explore modes of writing about architecture both within and beyond the discipline. The collection represents a broad range of geographical and cultural positions including indigenous and non-Western contexts, and includes a foreword and afterword by important thinkers in the domains of architectural criticism (Jane Rendell) and cultural studies/ethnography (Stephen Muecke).
1. Prelude : the ways in which we write / Jane Rendell -- 2. Waking Ideas From Their Sleep : An introduction to ficto-critical writing in and of architecture / Hélene Frichot and Naomi Stead -- 3. From Site to Situation : Cutting up as fictocritical composition / Anna Gibbs -- 4. Construction (and connection) / Katrina Schlunke -- 5. Incompossible Constructions of an Island Paradise / Hélène Frichot -- 6. Archaeologies of Exile on Trikeri Island : Listening to stones and speculating on prison matters / Elke Krasny and Phoebe Giannisi -- 7. In which Robert Smithson visits Christchurch : Ficto-criticism and the field trip / Jacky Bowring -- 8. Hiroshima : Notes of the expanded field / Kim Roberts -- 9. Writing Walking : Ficto-critical routes through eighteenth-century London / Emma Cheatle -- 10. The Indelible Traces of Your Footsteps / Mireille Roddier -- 11. Sydney Letters : A to E / Naomi Stead and Katrina Schlunke -- 12. Outrage on Calle de Alcala / Scott Colman and Lars Lerup -- 13. Architecture as Entourage : The politics of objects / Michael Young -- 14. The Architect Who Couldn't Write / Keith Mitnick -- 15. Return to Cold Spring Harbor Laboratory after The Marriage Plot / Sandra Kaji-O'Grady -- 16. The Bannister / Katrina Simon -- 17. Nice House, Woodland Lakes / Andrew Steen -- 18. The Door Left Ajar : On Dissident Waiting and Collective Fiction / Sepideh Karami -- 19. Postlude : Ficto-criticism after critique / Stephen Muecke.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Hélène Frichot is Professor of Architecture and Philosophy and Director of the Bachelor of Design at the University of Melbourne, Australia. Naomi Stead is Professor of Architecture and Head of the Department of Architecture at Monash University, Australia and Adjunct Professor in the School of Architecture at the University of Queensland, Australia.
Print version record.
eBooks on EBSCOhost
Keywords: Architectural criticism; Critical discourse analysis; Literature -- Aesthetics; Critique d'architecture.; Analyse critique du discours; Littérature -- Esthétique.; architectural criticism; Theory of architecture; Architectural criticism; Critical discourse analysis; Literature -- Aesthetics